1995
DOI: 10.1111/j.0022-3646.1995.00922.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF DISSOLVED OXYGEN PARTIAL PRESSURE ON THE ACCUMULATION OF ASTAXANTHIN IN CHEMOSTAT CULTURES OF HAEMATOCOCCUS LACUSTRIS (CHLOROPHYTA)

Abstract: The effect of dissolved oxygen partial pressure on the accumulation of astaxanthin in the green alga Haematococcus lacustris (Gir.) Rostaf (UTEX16) was studied in N‐limited continuous chemostat cultures. The steady‐state astaxanthin content measured against culture volume, cell number, and biomass dry weigh of Haematococcus cultures was proportional to the dissolved O2 partial pressure in the culture medium, over the range of 0–50% O2 The steady‐state biomass dry weight concentrations remained at between 0.52 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 8 publications
0
4
1
Order By: Relevance
“…4B). This value was higher than those reported by Lee and Ding (1995) Lee and Soh (1991) Under nitrate saturating conditions, the elemental composition of dry biomass (46.7% C, 8.0% N, 6.7% H) was fairly constant (Table I), the C/N ratio being close to 5.7. Under nitrate-limiting conditions, however, the nitrogen content of cells decreased significantly.…”
Section: Resultscontrasting
confidence: 58%
See 1 more Smart Citation
“…4B). This value was higher than those reported by Lee and Ding (1995) Lee and Soh (1991) Under nitrate saturating conditions, the elemental composition of dry biomass (46.7% C, 8.0% N, 6.7% H) was fairly constant (Table I), the C/N ratio being close to 5.7. Under nitrate-limiting conditions, however, the nitrogen content of cells decreased significantly.…”
Section: Resultscontrasting
confidence: 58%
“…Accumulation of astaxanthin in H. pluvialis has been studied by a number of groups (Boussiba, 2000;Boussiba and Vonshak, 1991;Fábregas et al, 2001Fábregas et al, , 2003Harker et al, 1995;Kobayashi et al, 1991Kobayashi et al, , 1992aLee and Ding, 1995;Lee and Soh, 1991;Orosa et al, 2001;Zlotnik et al, 1993). The main general conclusions from these works are: (i) in order to induce astaxanthin accumulation, growth should be slowed-down or stopped; (ii) the astaxanthin accumulation rate increases with irradiance; and (iii) the kinetics of astaxanthin accumulation varies with the nature of the stress condition imposed.…”
Section: Introductionmentioning
confidence: 99%
“…to irradiance and UV are mediated by the production of these molecules from oxygen generated during photosynthesis. Furthermore, high oxygen concentrations have been show to increase intracellular concentration of antioxidants such as astaxanthin in Haematococcus lacutris (Lee and Ding 1995) and result in increased antioxidant enzyme levels in Symbiodinium microadriaticum (Matta and Trench 1991). Other studies, however, have shown little effect of high oxygen tensions on a number of cultured microalgae.…”
mentioning
confidence: 99%
“…The strains that exhibited the most varied results were CCM-UDEC 022 and CCM-UDEC 023. In fact, CCM-UDEC 022 showed the highest division rates (0.97 div day -1) and the highest cell densities (4.4 x 10 5 cells ml -1 ) under autotrophic conditions on day 14; both parameters were much higher than the normal range found in the literature for the species (0.5-0.7 div day -1 and 1.5-2.5 x 10 5 cell ml -1 , Hagen et al 1993, Lee & Ding 1994, 1995, Harker et al 1996, Orosa et al 2001. The CCM-UDEC 023 strain, in contrast, exhibited lower division rates than CCM-UDEC 022 (ca.…”
Section: Discussionmentioning
confidence: 58%
“…Although considerable information exists regarding the factors that promote growth (i.e. Kobayashi et al 1991, Barbera et al 1993, Zlotnik et al 1993, Fan et al1994, Lee & Ding 1995, Harker et al 1996, Gong & Chen 1997, Triphathi et al 1999, Hagen et al 2001, Orosa et al 2001, García-Malea et al 2005, Jeon et al 2006 and astaxanthin accumulation (review in Boussiba 2000, Domínguez-Bocanegra et al 2004, García-Malea et al 2005, Orosa et al 2005 in H. pluvialis, most of the studies have looked at single strains mainly from culture collections (i.e., UTEX, NIES, CCAP, ATCC, SAG, NIVA) and examined under a wide range of culture conditions.…”
Section: Introductionmentioning
confidence: 99%